Are General Dental Practitioners Providing Best Practice in Prevention – in Everyday General Practice?. Issue 3 (September 2013) - Pearce, Mark; Catleugh, Melanie
Aims: To discover whether general dental practitioners are providing best practice in prevention, as defined by the 'Delivering Better Oral Health' toolkit, in everyday general practice. Method: A questionnaire was created with five scenarios describing the key findings of the examination of five hypothetical patients. Dentists attending a postgraduate meeting were asked to list all the preventive treatment and advice they would give each patient. The content of their answers was compared with the toolkit by two researchers. Results: Twenty four dentists completed the questionnaire. In general terms, they did not mention much of the specific advice or recommend the treatment listed in the toolkit except that a significant proportion would apply fluoride varnish to children's teeth and all would give smoking cessation advice where appropriate. Suitable recall intervals, defined by the National Institute for Clinical Excellence, were suggested for three of the scenarios but the advice was inconsistent for the other two scenarios. Conclusion: This small investigation suggests that dentists' implementation of prevention, as advised by the toolkit, is not thorough or consistent. Comprehensive adoption of prevention in dentistry will require intensive multifaceted education and organisational change such as might be provided by the new contracts being piloted at present.